Effect of nutritional intervention on body composition and performance in elite athletes - Garthe, I.; Raastad, T.; Refsnes, P. E.; Sundgot-Borgen, J. (European Journal of Sport Science, 2013)
Strength training and positive energy intake are the most important factors related to lean body mass (LBM) gain. Most studies investigating weight-gain interventions are based recreationally active subjects and less is known about optimal weight-gain protocols in elite athletes. The purpose of this study was to evaluate the effect of nutritional guidance in an 8- to 12-week weight-gain period in elite athletes. Thirty-nine elite athletes were randomised to either a `nutritional counseling group` (NCG, n=21, 19.1±2.9 years, 70.9±8.9 kg) or `ad libitum group` (ALG, n=18, 19.6±2.7 years, 75.0±5.9 kg). All athletes continued their sport-specific training which included an additional four strength-training sessions per week. NCG followed a meal plan providing a positive energy balance, while the ALG athletes had an ad libitum energy intake. Body weight (BW), body composition, one repetition maximum (1RM), 40 m sprint and counter movement jump (CMJ) were measured pre- and post-intervention. Energy intake was higher in the NCG than in the ALG (3585±601 vs. 2964±884 kcal) and consequently BW increased more in NCG than in ALG (3.9±0.6% vs. 1.5±0.4%). Fat mass (FM) increased more in NCG than in ALG (15±4 vs. 3±3%), but gain in LBM was not different between groups. All 1RM results improved in both groups (6-12%), whereas 40 m sprint and CMJ remained unchanged, except for a significant decrease in 40 m sprint for the athletes in NCG. Athletes with nutritional guidance increased BW more, however, excess energy intake in a weight-gain protocol should be considered carefully due to undesirable increases in body fat.